Comparison of Mid-term Outcome of Multivessel Percutaneous Coronary Intervention with Drug Eluting Stents in Patient with Chronic Coronary Syndrome between Diabetic and Non-diabetic Groups (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: In Bangladesh, the prevalence of chronic coronary syndrome is rising which results in more revascularization with percutaneous coronary intervention (PCI), especially multi-vessel PCI. Although post-procedure patient outcomes are improving, co-morbidities and risk factors, such as diabetes, raise questions about the procedure's efficacy and longevity.Objective: To compare the mid-term (6-month) results of drug- eluting stent multi-vessel percutaneous coronary intervention in patients with Chronic Coronary Syndrome in groups with and without diabetes.Methods: This study was conducted at the cardiology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) on 100 patients who underwent multivessel PCI six months earlier. In both diabetes and non-diabetic individuals, the study evaluated major adverse cardiac events (MACE), clinical state and functional ability. A data collecting sheet was used to gather information and patient privacy was protected. Comparing outcome variables between patients with and without diabetes before and after six months was the goal of the study.Results: The average age (with standard deviation) of diabetic patients (53.3±8.81) diagnosed with Chronic Coronary Syndrome was less than that of non-diabetic patients (54.9±8.06). All initial characteristics were comparable between the two groups, except for functional class (NYHA) and the extent of vessel involvement. The occurrence of triple vessel disease was higher in diabetic patients than in non-diabetic patients with SIHD, although the difference was not statistically significant. The average number of stents placed per patient (2.4±0.48 vs 2.3±0.55) was greater in non-diabetic patients compared to diabetic patients with SIHD, but this difference was also statistically insignificant. The rates of in-hospital adverse outcomes, which included death from cardiovascular reasons, periprocedural myocardial infarction, hyperacute stent thrombosis, CIN and bleeding complications, showed no significant differences between the two groups. Even though MACCE were frequently observed in the diabetic group at the 6-months, these results were not statistically significant. A statistically significant positive impact on clinical status (as measured by CCS class and NYHA class) and functional status (indicated by METS) was evident at 6 months following multivessel PCI in both the diabetic and non-diabetic groups. An assessment of LV systolic function and renal function demonstrated similarstable cardiorenal conditions in both groups. However, diabetic patients exhibited a significantly higher serum creatinine level compared to their baseline measurement.Conclusion: In both the diabetic and non-diabetic patient groups, multivessel PCI with drug-eluting stents for chronic coronary syndrome has comparable favorable in-hospital and mid-term outcomes with respect to MACE, clinical status (CCS class, NYHA class), functional status (METS), LV systolic function (LVEF), and renal function (serum creatinine). When comparing diabetes groups to non-diabetic groups, there was a noticeable increase in serum creatinine and medically treated angina.JAFMC Bangladesh, Vol 21, No 1 (June)2025:44-51